1992
DOI: 10.1016/0378-1097(92)90055-s
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of macrophage susceptibility to infection by Legionella pneumophila

Abstract: Legionella pneumophila readily grows in cultures of thioglycollate (TGC)‐induced macrophages (MPs) from A/J mice, but not in MPs from BALB/c mice or other mouse strains. In the present study, the growth of Legionella pneumophila in MPs from A/J and BALB/c mice, as well as hybrids of the two strains and back‐crossed mice, was investigated to determine whether the permissiveness of growth of these bacteria was due to an inherited trait of the MPs. The MPs from all A/J mice supported the growth of Legionella, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Interestingly, the dot/icm genes delay uptake and induce macropinocytosis in A/J mouse macrophages [14]. With the exception of A/J mice, most of the inbred mouse strains are not permissive to L. pneumophila infection; neither are macrophages isolated from these mice [40,41]. Macropinosomes containing L. pneumophila in A/J mouse macrophages are induced transiently and shrink rapidly (5-15 min) [14], and this mode of uptake is linked to the lgn1 locus on chromosome 13 of mice [14,42,43].…”
Section: Adherence and Entry Into Mammalian Cellsmentioning
confidence: 98%
“…Interestingly, the dot/icm genes delay uptake and induce macropinocytosis in A/J mouse macrophages [14]. With the exception of A/J mice, most of the inbred mouse strains are not permissive to L. pneumophila infection; neither are macrophages isolated from these mice [40,41]. Macropinosomes containing L. pneumophila in A/J mouse macrophages are induced transiently and shrink rapidly (5-15 min) [14], and this mode of uptake is linked to the lgn1 locus on chromosome 13 of mice [14,42,43].…”
Section: Adherence and Entry Into Mammalian Cellsmentioning
confidence: 98%
“…Macrophages derived from many inbred mouse strains have been shown to be restrictive or permissive of L. pneumophila intracellular growth, with the C57BL/6J (B6) strain being used as the canonical restrictive strain (9,42,43). A/J, a permissive mouse strain, supports 10 3 -to 10 4 -fold growth of L. pneumophila over a 3-day period, whereas B6 rarely supports Ͻ10-fold growth over this time period (9,42,43).…”
mentioning
confidence: 99%
“…A/J, a permissive mouse strain, supports 10 3 -to 10 4 -fold growth of L. pneumophila over a 3-day period, whereas B6 rarely supports Ͻ10-fold growth over this time period (9,42,43). Studies involving crosses of B6 and A/J showed that restriction of L. pneumophila growth is dominant and segregates in a Mendelian fashion via a single autosomal locus on mouse chromosome 13 named Lgn1 (5,9).…”
mentioning
confidence: 99%
“…Summersgill et al [10] found that induced nitric oxide synthase activity in RAW 264.7 cells, a murine macrophage cell line, was correlated with killing of L. pneumophila and depletion of intracellular iron. Since the mechanism explaining the differences in susceptibility among macrophages from different mouse strains remains to be determined [11,12], we studied the role of iron in macrophages from two mouse strains which differ in permissiveness to intracellular L. pneumophila growth.…”
Section: Introductionmentioning
confidence: 99%